2016
DOI: 10.7897/2230-8407.04403
|View full text |Cite
|
Sign up to set email alerts
|

Cronobacter Sakazakii: An Emerging Contaminant in Pediatric Infant Milk Formula

Abstract: Cronobacter sakazakii (C. sakazakii) previously known as Enterobacter sakazakii is a motile, Gram-negative, non-sporing yellow pigmented rod, which belongs to lethal Enterobacteriaceae family. C. sakazakii is ubiquitously found in air, soil, floor drains, and dry product processing environment. It has been isolated from hospitals, clinical materials, and cutting fluids and is also present in cerebrospinal fluid (CSF), blood, sputum, throat, nose, stool, gut, skin, wounds, bone marrow, eye, ear and breast absce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0
4

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
(60 reference statements)
1
0
0
4
Order By: Relevance
“…C.sakazakii it is an opportunistic human and food-borne pathogen. The organism can be found in broad range of food including powdered infant formula (PIF) , cheese, meat, vegetables, grain, herbs , spices , tomato , water and households [23,24] These results coincides with pervious study which shown that Lactobacillus acidophilus has ability to inhibit and safe bio-preservative protect infants from C.sakazakii [25,26].…”
Section: Antimicrobial Effect Of Lacidophilus Against Three Isolatedsupporting
confidence: 75%
“…C.sakazakii it is an opportunistic human and food-borne pathogen. The organism can be found in broad range of food including powdered infant formula (PIF) , cheese, meat, vegetables, grain, herbs , spices , tomato , water and households [23,24] These results coincides with pervious study which shown that Lactobacillus acidophilus has ability to inhibit and safe bio-preservative protect infants from C.sakazakii [25,26].…”
Section: Antimicrobial Effect Of Lacidophilus Against Three Isolatedsupporting
confidence: 75%
“…De acordo com Arsalan et al 5 , a fabricação de FLi comercialmente estéreis nem sempre é possível de ser realizada utilizando-se a tecnologia de processamento atual. Com isso, existem riscos potenciais de infecção dos bebês através do consumo deste alimento.…”
Section: Introductionunclassified
“…Cronobacter spp. (antigamente descrito como Enterobacter sakazakii) e Salmonella enterica são os mais preocupantes patógenos associados às fórmulas lácteas, uma vez que existem claras evidências de que suas presenças podem resultar em graves doenças na população de risco que consome esse alimento 5,6,8 .…”
Section: Introductionunclassified
“…Os micro-organismos que geralmente são isolados de fórmulas infantis em pó são Cronobacter sakazakii, Salmonella enterica, Staphylococcus aureus, Bacillus cereus, Clostridium difficile, Clostridium perfringens, Clostridium botulinum, Listeria monocytogenes e Klebsiella pneumoniae (FAO/ WHO, 2008;ARSALAN et al, 2013a).…”
Section: Sumário 1 Introduçãounclassified
“…Padrões industriais vêm sendo estabelecidos para garantir a segurança e estabilidade microbiológica das fórmulas infantis em pó (ARSALAN et al, 2013a). Nas últimas décadas houve um crescente interesse e esforço para o desenvolvimento de ferramentas mais eficientes para o controle microbiológico, acatando as exigências de programas de alimentos seguros, especialmente aqueles destinados a recém-nascidos e crianças (International Commission on Microbiological Specification for Foods [ICMSF], 2006).…”
Section: Sumário 1 Introduçãounclassified